A Compact Wideband Stacked Antenna for the Tri-Band GPS Applications. (19th October 2008) - Abd Elrazzak, Maher M.; Alsharekh, M. F.
Abstract : A compact wideband stacked patch antenna is presented for the applications of GPS systems. This antenna covers the L1, L2, and L5 GPS bands of operating frequencies 1.575, 1.227, and 1.176 GHz, respectively. High permittivity dielectric materials are used to minimize the antenna dimensions. The obtained antenna is of dimensions32 × 18 × 2.117  mm. To verify the design, the time dependence field distribution, the scattering parameters, and the radiation pattern are presented. The scattering parameters show that the antenna operates at the GPS frequencies with lower than− 10  dB. The finite difference time domain (FDTM) with the perfect matched layer (PML) is used in the present analysis.